The Sensory and Perceptual Scaffolding of Absorption, Inner Speech, and Self in Psychosis - Rosen, Cherise; Tufano, Michele; Humpston, Clara S.; Chase, Kayla A.; Jones, Nev; Abramowitz, Amy C.; Franco Chakkalakal, Ann; Sharma, Rajiv P. (Frontiers in Psychiatry, 2021)
This study examines the interconnectedness between absorption, inner speech, self, and psychopathology. Absorption involves an intense focus and immersion in mental imagery, sensory/perceptual stimuli, or vivid imagination that involves decreased self-awareness and alterations in consciousness. In psychosis, the dissolution and permeability in the demarcation between self and one's sensory experiences and perceptions, and also between self-other and/or inter-object boundaries alter one's sense of self. Thus, as the individual integrates these changes new “meaning making” or understanding evolves as part of an ongoing inner dialogue and dialogue with others. This study consisted of 117 participants: 81 participants with psychosis and 36 controls. We first conducted a bivariate correlation to elucidate the relationship between absorption and inner speech. We next conducted hierarchical multiple regressions to examine the effect of absorption and inner speech to predict psychopathology. Lastly, we conducted a network analysis and applied extended Bayesian Information Criterion to select the best model. We showed that in both the control and psychosis group dialogic and emotional/motivational types of inner speech were strongly associated with absorption subscales, apart from the aesthetic subscale in the control group which was not significant, while in psychosis, condensed inner speech was uniquely associated with increased imaginative involvement. In psychosis, we also demonstrated that altered consciousness, dialogic, and emotional/motivational inner speech all predicted positive symptoms. In terms of network associations, imaginative involvement was the most central, influential, and most highly predictive node in the model from which all other nodes related to inner speech and psychopathology are connected. This study shows a strong interrelatedness between absorption, inner speech and psychosis thus identifying potentially fertile ground for future research and directions, particularly in the exploration into the underlying construct of imaginative involvement in psychotic symptoms.